2022
DOI: 10.3390/foods11070946
|View full text |Cite
|
Sign up to set email alerts
|

Use of Food Spoilage and Safety Predictor for an “A Priori” Modeling of the Growth of Lactic Acid Bacteria in Fermented Smoked Fish Products

Abstract: Fermentation is one of the oldest methods to assure the safety and quality of foods, and to prolong their shelf life. However, a successful fermentation relies on the correct kinetics depending on some factors (i.e., ingredients, preservatives, temperature, inoculum of starter cultures). Predictive microbiology is a precious tool in modern food safety and quality management; based on the product characteristics and the conditions occurring in food processing, the inactivation of or increase in microbial popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Conditions present in a food environment as well as the effect of the smoking-process method used, could affect the growth and antimicrobial activity of LAB. Moreover, Racioppo et al [ 90 ] used the Food Spoilage and Safety Predictor (FSSP) to model the effect of temperature, salt, liquid smoke, CO 2 , and nitrites on the growth of LAB in fermented smoked fish products, demonstrating that liquid smoke, followed by temperature and salt had the strongest effect on the fermentation process. Uyttendaele et al [ 72 ] reported growth limitation of L. monocytogenes in smoked fish when combining low pH (5.5–6), and low a w (0.93–0.94).…”
Section: Resultsmentioning
confidence: 99%
“…Conditions present in a food environment as well as the effect of the smoking-process method used, could affect the growth and antimicrobial activity of LAB. Moreover, Racioppo et al [ 90 ] used the Food Spoilage and Safety Predictor (FSSP) to model the effect of temperature, salt, liquid smoke, CO 2 , and nitrites on the growth of LAB in fermented smoked fish products, demonstrating that liquid smoke, followed by temperature and salt had the strongest effect on the fermentation process. Uyttendaele et al [ 72 ] reported growth limitation of L. monocytogenes in smoked fish when combining low pH (5.5–6), and low a w (0.93–0.94).…”
Section: Resultsmentioning
confidence: 99%